STRATEGY AND DEVELOPMENT OF THE GAMBIR INNOVATION SYSTEM FOR THE PEOPLE'S ECONOMY (CASE STUDY OF 50 CITIES DISTRICT) - Meilisa, Meilisa; Tan, Firwan (Transpublika Publisher, 2024)
This research seeks to formulate an elaborate diversification strategy for processed Gambir products, aiming to enhance the overall well-being of the community residing in District 50 of West Sumatra City. Employing a descriptive qualitative approach, this study adopts a case study research design, delving into the subject matter comprehensively and extensively through the utilization of diverse data sources. The primary focus lies on conducting a meticulous examination of Gambir farmers and industries within the confines of District 50, West Sumatra, utilizing innovative techniques to bring about the diversification of Gambir products. The data collection process involves keen observation of Gambir farmers and the industrial landscape, encompassing a range of activities within the 50 City Regency of West Sumatra. The introduction of innovation, specifically the diversification of Gambir, is anticipated to yield additional value from the traditionally cultivated crop. Beyond the conventional production of raw and dry Gambir products, this research aims to empower farmers to venture into the production of derivative products. The overarching goal is to foster a sustainable and diversified Gambir industry that not only meets the immediate needs of the farmers but also contributes to the broader economic landscape of District 50, West Sumatra City. By fostering innovation and expanding the product range, this research aspires to create a ripple effect, ultimately resulting in a positive impact on the socio-economic status of Gambir farmers in the target district.